The A-center defect in diamond: quantum mechanical characterization through the infrared spectrum. Issue 22 (23rd May 2017) - Salustro, Simone; Sansone, Giuseppe; Zicovich-Wilson, Claudio M.; Noël, Yves; Maschio, Lorenzo; Dovesi, Roberto
Abstract : The A-center in diamond, which consists of two nitrogen atoms substituting two neighboring carbon atoms, has been investigated at the quantum mechanical level using an all-electron Gaussian type basis set, hybrid functionals and the periodic supercell approach. Abstract : The A-center in diamond, which consists of two nitrogen atoms substituting two neighboring carbon atoms, has been investigated at the quantum mechanical level using an all-electron Gaussian type basis set, hybrid functionals and the periodic supercell approach. In order to simulate different defect concentrations, four supercells have been considered containing 32, 64, 128 and 216 atoms, respectively. The ground state is a closed shell system where the two neighboring nitrogen atoms are separated, as a consequence of the strong repulsive interaction between the lone pairs, by 2.22 Å. The calculated band gap of a perfect diamond is 5.75 eV, which is in very good agreement with the experimental value of 5.80 eV (at 0 °K); the vertical electronic transition energy from the defective band to the conduction band is 4.75 and 4.46 eV for the cells containing 128 and 216 atoms, respectively. The presence of the A-center does not affect the Raman spectrum of diamond. Several intense peaks appear on the contrary in the IR spectrum, which permit (or should permit) the identification of this defect. The four peaks proposed by Sutherland et al. ( Nature, 1954, 174, 901–904) and widely accepted as fingerprints of the A-center (at 480, 1093, 1203, 1282 cm −1 ), and the most important features of the spectrum published by Davies 22 years later ( J. Phys. C: Solid State Phys., 1976, 9, 537–542) are very well reproduced by our simulated spectrum with the largest supercell. The modes in which the nitrogen atoms are more involved are identified by the frequency shift due to the 14 N → 15 N isotopic substitution; the two modes corresponding to the experimental ones at 480 and 1282 cm −1 show the largest isotopic shift. The graphical animation of the modes (available at ; Web:http://www.pmmp.jussieu.fr/yves/Jmolvib/?name=A_freq.xyz&spt=A_freq.spt ) not only confirms this attribution, but permits also the investigation of the nature of the full set of modes.